Perancangan Sistem Informasi Lembaga Keuangan Mikro Agrobisnis (LKMA) Prima Agung Kanagarian Sungai Duo Kecamatan Sitiung Kabupaten Dharmasraya - stephane, Ilfa; Saputra, Heru (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2017)
Microfinance Institutions Agribusiness (LKMA) Prima Agung Kenagarian Sungai Duo Kecamatan Sitiung Kabupaten Dharmasraya  is one form of cooperatives engaged in the field of micro-credit. In management, conventional systems are still used in the form of a book. This method is less effective for savings and loan transactions in large quantities because it required precision in processing accounting data such as repetition of writing that can lead to wastage of working time. With the existence of these problems, LKMA Prima Agung needs to use a savings and loan applications that can assist in data processing. The research method used in this study is the identification of the problem, literature, and the establishment of data collection, system design, analysis, design and implementation of the system. The results of this study are expected to be an alternative solution, especially for LKMA Prima Agung in completing various transaction processes effectively and efficiently.
Keywords: LKMA Prima Agung; Sistem Informasi